1T-phase molybdenum disulfide-based composite catalytic material as well as preparation method and application thereof
By using a 1T phase molybdenum disulfide-based composite catalytic material with a core-shell structure, the problems of thermodynamic instability and limited catalytic active sites are solved, and efficient catalytic and electrochemical performance improvements are achieved.
Patent Information
- Application Number
- CN202411437803.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-17
AI Technical Summary
The 1T phase molybdenum disulfide catalytic material is thermodynamicly unstable and is easily converted to 2H phase at room temperature, resulting in limited catalytic active sites and limiting its catalytic efficiency.
It adopts a microsphere composite catalytic material with a core-shell structure. The core is composed of nickel disulfide nanosheet crystals. The spherical shell is composed of thermodynamically stable 1T phase molybdenum disulfide nanosheets. The flower-shaped molybdenum disulfide nanosheets are perpendicular to the surface of the microsphere. Form a three-dimensional network structure.
The thermodynamic stability of 1T phase molybdenum disulfide is achieved, the active sites in the basal plane and edges are enriched, the catalytic efficiency and electrochemical performance are improved, and the material shuttle effect in the electrolyte is effectively blocked.
Smart Images

Figure CN119318975A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite catalytic material and a preparation method and application thereof. Background Art
[0002] Molybdenum disulfide is a typical two-dimensional layered material. Due to its excellent electrocatalytic performance, low price and abundant reserves, it has great application potential in the field of catalysis and has therefore received widespread attention. Generally speaking, the thermodynamically stable state of MoS2 is the 2H phase, which is a semiconductor with poor electrical conductivity. Moreover, as a typical two-dimensional material, the number of basal atoms in MoS2 is far greater than the number of edge atoms. The atoms in the basal plane of 2H phase MoS2 are usually inert atoms and have no catalytic activity, so the catalytic active sites of 2H phase MoS2 are limited, which greatly limits its catalytic efficiency. In addition, two-dimensional materials have the disadvantage of easy agglomeration, resulting in more active sites that cannot be exposed, thereby greatly reducing the catalytic activity of the material. In contrast, 1T phase MoS2 is a metallic phase with good electrical conductivity, and the atoms in its basal plane also have catalytic activity, which can effectively improve the utilization rate of atoms in MoS2 materials. However, 1T phase MoS2 is thermally metastable and will gradually transform into 2H phase even at room temperature. Therefore, how to obtain stable 1T phase molybdenum disulfide has become a research hotspot for technicians in the field of catalysis. Summary of the invention
[0003] The purpose of the present invention is to solve the problem that 1T phase molybdenum disulfide catalytic material is thermodynamically unstable and will gradually transform into 2H phase even at room temperature. The catalytic active sites of 2H phase molybdenum disulfide are limited, which greatly limits its catalytic efficiency. A 1T phase molybdenum disulfide-based composite catalytic material, a preparation method and application thereof are provided.
[0004] A 1T phase molybdenum disulfide-based composite catalytic material is a micron ball with a core-shell structure, with a diameter of 1.5μm to 5.0μm, wherein the core is a compact sphere composed of nickel disulfide nano-flaky crystals, with a diameter of 1.0μm to 4.0μm, and the shell is a wrinkled and fluffy shell composed of thermodynamically stable 1T phase molybdenum disulfide nanosheets, with a thickness of 0.2μm to 1μm, and flower-shaped molybdenum disulfide nanosheets are perpendicular to the surface of the micron ball and wrapped in the outer layer to form a three-dimensional network structure; the lateral size of the flower-shaped molybdenum disulfide nanosheets is 50 to 800nm, the thickness is 5-30nm, and the (002) crystal plane spacing is 0.85 to 0.90nm, which is consistent with the 1T phase structure.
[0005] A method for preparing a 1T phase molybdenum disulfide-based composite catalytic material is specifically completed by the following steps:
[0006] 1. Preparation of nickel disulfide core:
[0007] First, Ni(NO3)2·6H2O is added to deionized water and stirred until dissolved, and then Na2S2O3·5H2O is added and stirred until dissolved to obtain a mixture; the mixture is poured into a high-pressure reactor, subjected to hydrothermal reaction for a period of time, cooled to room temperature, and then centrifugally washed and vacuum dried to recover the product to obtain a nickel disulfide spherical core;
[0008] 2. Preparation of 1T phase MoS2-based composite catalytic material:
[0009] Under ultrasonic conditions, nickel disulfide spherical cores are dispersed in ultrapure water, and then ammonium molybdate tetrahydrate and thiourea are added and stirred evenly to obtain a black mixed solution; the black mixed solution is poured into a high-pressure reactor, subjected to hydrothermal reaction for a period of time, cooled to room temperature, and then centrifuged and washed and vacuum dried to recover the product to obtain a 1T phase molybdenum disulfide-based composite catalytic material.
[0010] A 1T phase molybdenum disulfide-based composite catalytic material is used as a positive electrode host, a separator or an interlayer of a lithium-sulfur battery or a sodium-sulfur battery.
[0011] Advantages of the present invention:
[0012] 1. A thermodynamically stable 1T phase molybdenum disulfide-based composite catalytic material obtained by the present invention; 1T phase molybdenum disulfide is a typical two-dimensional layered material, which has abundant basal plane active sites and edge active sites, and can achieve good adsorption of reactants, thereby improving catalytic efficiency;
[0013] 2. A thermodynamically stable 1T phase molybdenum disulfide-based composite catalytic material obtained by the present invention; 1T phase molybdenum disulfide is a typical two-dimensional layered material, and the wider (002) crystal plane spacing is conducive to the embedding and conduction of ions, thereby obtaining good electrochemical performance;
[0014] 3. A thermodynamically stable 1T phase molybdenum disulfide-based composite catalytic material obtained by the present invention; 1T phase molybdenum disulfide is in a metallic state, has good electrical conductivity, can provide faster charge transfer performance, thereby promoting the reaction and obtaining good catalytic performance;
[0015] 4. A thermodynamically stable 1T phase molybdenum disulfide-based composite catalytic material obtained by the present invention; the composite material selects nickel disulfide as the substrate for the growth of molybdenum disulfide nanosheets, thereby avoiding the stacking and agglomeration of molybdenum disulfide nanosheets; at the same time, the molybdenum disulfide nanosheets grow perpendicular to the surface of the microspheres, forming a three-dimensional network structure between each other, which is conducive to the infiltration and penetration of the electrolyte and promotes the occurrence of chemical reactions; moreover, the three-dimensional network structure can effectively block the shuttling effect of substances in the electrolyte;
[0016] 5. A thermodynamically stable 1T phase molybdenum disulfide-based composite catalytic material obtained by the present invention; the composite material selects nickel disulfide as the substrate for the growth of molybdenum disulfide nanosheets, which provides a guarantee for the thermodynamic stability of the 1T phase structure of molybdenum disulfide; at the same time, nickel disulfide is composed of small-sized nano-platelet crystals rather than dense bulk crystals, which is conducive to the infiltration and penetration of the electrolyte and the rapid transmission of ions in the electrolyte, thereby ensuring good electrochemical catalytic performance;
[0017] 6. A thermodynamically stable 1T phase molybdenum disulfide-based composite catalytic material obtained by the present invention; the composite material selects nickel disulfide as a substrate for the growth of molybdenum disulfide nanosheets, and the nickel disulfide core and the molybdenum disulfide shell work synergistically to improve the overall catalytic performance of the material;
[0018] 7. A thermodynamically stable 1T phase molybdenum disulfide-based composite catalytic material obtained by the present invention; the composite material contains a small amount of N element; the introduction of N element can significantly increase the binding energy of the composite surface, polarize the surface, generate dipoles, and form dipole-dipole electrostatic interactions with polar substances, ultimately providing sufficient surface binding force and restriction effect on polar substances, reducing material loss;
[0019] 8. A thermodynamically stable 1T phase molybdenum disulfide-based composite catalytic material obtained by the present invention; its preparation process is ingenious, the processing equipment is inexpensive, the procedure and method are simple, the cost is low, and it is conducive to large-scale industrial production;
[0020] 9. A thermodynamically stable 1T phase molybdenum disulfide-based composite catalytic material obtained by the present invention; a commercial polypropylene diaphragm modified by the material is applied to lithium-sulfur batteries, the shuttle effect is well suppressed, and good electrochemical performance is obtained; at 0.1C, the capacity is 1437mAh g -1 ; Under 5C conditions, the capacity is 722mAhg -1 When the current density returns to 0.1C, the capacity can still reach 1230mAh g -1 ; Under 0.2C conditions, 1228mAhg -1 The initial capacity of the battery can be maintained at 85% after 100 cycles; the initial capacity is 1154 mAh g at 0.5C. -1 During the 250-cycle cycle, the decay rate per cycle is only 0.099%; under 1C conditions, the initial capacity is 931mAhg -1 During the 1000-cycle cycle, the attenuation rate per cycle is only 0.051%. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a low-magnification scanning electron microscope image of the nickel disulfide spherical core prepared in Example 1;
[0022] Figure 2 This is a scanning electron microscope image of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1;
[0023] Figure 3 The X-ray diffraction spectrum of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1;
[0024] Figure 4 This is the selected area electron diffraction pattern of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1;
[0025] Figure 5 The composition analysis results of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1;
[0026] Figure 6 This is a transmission electron microscope image of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1;
[0027] Figure 7 This is the full XPS spectrum of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1;
[0028] Figure 8 This is the Raman spectrum of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1;
[0029] Fig. 9 The X-ray diffraction spectra of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1 before and after being placed for 360 days;
[0030] Fig.10 This is the X-ray diffraction spectrum of 1T phase MoS2 material (without NiS2 ball as substrate) before and after 90 days of storage;
[0031] Fig.11 Digital photos of the 1T phase molybdenum disulfide-based composite catalyst material, MoS2, and Li2S6 solution prepared in Example 1 before and after standing for 3 hours;
[0032] Fig.12 is the nucleation curve of lithium sulfide (Li2S) with carbon paper (CP) as electrode;
[0033] Fig.13 The nucleation curve of lithium sulfide (Li2S) of the 1T phase molybdenum disulfide-based composite catalytic material whose electrode is prepared in Example 1;
[0034] Fig.14 Thermogravimetric curve of C / S cathode;
[0035] Fig.15 The CV curves of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1 are modified diaphragm lithium-sulfur battery, MoS2-modified diaphragm lithium-sulfur battery and PP diaphragm lithium-sulfur battery;
[0036] Fig.16 The impedance spectra of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1 are modified diaphragm lithium-sulfur battery, MoS2-modified diaphragm lithium-sulfur battery and PP diaphragm lithium-sulfur battery;
[0037] Fig.17 The rate characteristics of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1 are modified diaphragm lithium-sulfur battery, MoS2-modified diaphragm lithium-sulfur battery and PP diaphragm lithium-sulfur battery;
[0038] Fig.18 The cycle characteristics of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1 are modified diaphragm lithium-sulfur battery, MoS2-modified diaphragm lithium-sulfur battery and PP diaphragm lithium-sulfur battery;
[0039] Fig.19 Performance diagram of the battery assembled by preparing a diaphragm and assembling a battery using 1T-phase molybdenum disulfide-based composite catalytic material prepared by changing the Mo:Ni ratio, where (a) is the cycle performance and (b) is the initial capacity and capacity retention rate at 0.1C. DETAILED DESCRIPTION
[0040] Specific implementation method 1: In this implementation method, a 1T phase molybdenum disulfide-based composite catalytic material is a micron-sphere with a core-shell structure, with a diameter of 1.5μm to 5.0μm, the core of the sphere is a compact sphere composed of nickel disulfide nanosheet crystals, with a diameter of 1.0μm to 4.0μm, and the shell is a wrinkled and fluffy shell composed of thermodynamically stable 1T phase molybdenum disulfide nanosheets, with a shell thickness of 0.2μm to 1μm, and the flower-shaped molybdenum disulfide nanosheets are perpendicular to the surface of the micron-sphere and wrapped in the outer layer, forming a three-dimensional network structure with each other; the lateral size of the flower-shaped molybdenum disulfide nanosheets is 50 to 800nm, the thickness is 5-30nm, and the (002) crystal plane spacing is 0.85 to 0.90nm, which is consistent with the 1T phase structure.
[0041] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the molar ratio of nickel disulfide to molybdenum disulfide in the 1T phase molybdenum disulfide-based composite catalytic material is (1-3): (1-2), and the material contains a small amount of N element. The other steps are the same as those in specific embodiment 1.
[0042] Specific implementation method three: This implementation method is a method for preparing a 1T phase molybdenum disulfide-based composite catalytic material, which is specifically completed in the following steps:
[0043] 1. Preparation of nickel disulfide core:
[0044] First, Ni(NO3)2·6H2O is added to deionized water and stirred until dissolved, and then Na2S2O3·5H2O is added and stirred until dissolved to obtain a mixture; the mixture is poured into a high-pressure reactor, subjected to hydrothermal reaction for a period of time, cooled to room temperature, and then centrifugally washed and vacuum dried to recover the product to obtain a nickel disulfide spherical core;
[0045] 2. Preparation of 1T phase MoS2-based composite catalytic material:
[0046] Under ultrasonic conditions, nickel disulfide spherical cores are dispersed in ultrapure water, and then ammonium molybdate tetrahydrate and thiourea are added and stirred evenly to obtain a black mixed solution; the black mixed solution is poured into a high-pressure reactor, subjected to hydrothermal reaction for a period of time, cooled to room temperature, and then centrifuged and washed and vacuum dried to recover the product to obtain a 1T phase molybdenum disulfide-based composite catalytic material.
[0047] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the mass ratio of Ni(NO3)2·6H2O to deionized water in step 1 is (1 g to 2 g): 50 mL; the mass ratio of Na2S2O3·5H2O to deionized water in step 1 is (1.g to 2 g): 50 mL. The other steps are the same as those in specific embodiments 1 to 3.
[0048] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the temperature of the hydrothermal reaction in step 1 is 150°C to 170°C and the time of the hydrothermal reaction in step 1 is 19h to 21h. The other steps are the same as those in specific embodiments 1 to 4.
[0049] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: the centrifugal washing described in step 1 uses deionized water as a cleaning agent, centrifugal washing is performed 2 to 4 times, the speed of each centrifugal washing is 3000 r / min to 8000 r / min, and the time of each centrifugal washing is 5 min to 10 min; the temperature of the vacuum drying described in step 1 is 50°C to 70°C, and the time of the vacuum drying is 6 h to 24 h. The other steps are the same as those of specific embodiments 1 to 5.
[0050] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: the mass ratio of the nickel disulfide core described in step 2 to the volume ratio of ultrapure water is (0.2g-0.4g):100mL; the mass ratio of ammonium molybdate tetrahydrate described in step 2 to the volume ratio of ultrapure water is (0.5g-1.2g):100mL; the mass ratio of thiourea described in step 2 to the volume ratio of ultrapure water is (1.2g-1.7g):100mL. The other steps are the same as specific embodiments 1 to 6.
[0051] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the temperature of the hydrothermal reaction in step 2 is 170°C to 190°C and the time of the hydrothermal reaction in step 2 is 14h to 16h. The other steps are the same as those in specific embodiments 1 to 7.
[0052] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the centrifugal washing described in step 2 uses deionized water as a cleaning agent, the centrifugal washing is performed 2 to 4 times, the speed of each centrifugal washing is 1000 r / min to 10000 r / min, and the time of each centrifugal washing is 5 min to 20 min; the temperature of the vacuum drying described in step 2 is 50°C to 70°C, and the time of the vacuum drying is 6 h to 24 h. The other steps are the same as those of specific embodiments 1 to 8.
[0053] Specific embodiment ten: This embodiment is a 1T phase molybdenum disulfide-based composite catalytic material used as a positive electrode host, separator or interlayer of a lithium-sulfur battery or a sodium-sulfur battery.
[0054] The following examples are used to verify the beneficial effects of the present invention:
[0055] Embodiment 1: A method for preparing a 1T phase molybdenum disulfide-based composite catalytic material is specifically completed by the following steps:
[0056] 1. Preparation of nickel disulfide core:
[0057] First, 1.45 g of Ni(NO3)2·6H2O was added to 50 mL of deionized water and stirred until dissolved, and then 1.49 g of Na2S2O3·5H2O was added and stirred until dissolved to obtain a mixture; the mixture was poured into a high-pressure reactor, subjected to a hydrothermal reaction at 160° C. for 20 h, cooled to room temperature, and then centrifuged and washed 3 times with deionized water, and finally vacuum dried at 60° C. for 10 h, and the product was recovered to obtain a nickel disulfide spherical core;
[0058] The speed of each centrifugal washing is 6000r / min, and the time of each centrifugal washing is 10min;
[0059] 2. Preparation of 1T phase MoS2-based composite catalytic material:
[0060] Under ultrasonic conditions, 0.3 g of nickel disulfide core was dispersed into 100 mL of ultrapure water, and then 0.863 g of ammonium molybdate tetrahydrate and 1.487 g of thiourea were added and stirred evenly to obtain a black mixed solution; the black mixed solution was poured into a high-pressure reactor, hydrothermally reacted at 180°C for 15 h, cooled to room temperature, and then washed three times by deionization centrifugation, and finally vacuum dried at 60°C for 8 h, and the product was recovered to obtain a 1T phase molybdenum disulfide-based composite catalytic material (NiS2 / MoS2);
[0061] The rotation speed of each centrifugal washing is 6000r / min, and the time of each centrifugal washing is 10min.
[0062] The molar ratio of Mo:Ni in step 2 of Example 1 is 2:1.
[0063] Figure 1 This is a low-magnification scanning electron microscope image of the nickel disulfide spherical core prepared in Example 1;
[0064] from Figure 1 It can be seen that the core is a compact sphere composed of nanosheets with a diameter of 2.5 microns.
[0065] Figure 2 This is a scanning electron microscope image of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1;
[0066] from Figure 2 It can be seen that the composite catalytic material is a micron sphere with a core-shell structure, with a diameter of ~3 microns. The spherical shell is a wrinkled and fluffy spherical shell composed of nanosheets. The flower-like nanosheets are perpendicular to the surface of the micron sphere and wrapped in the outer layer, forming a three-dimensional network structure between each other, without stacking and agglomeration.
[0067] Figure 3 The X-ray diffraction spectrum of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1;
[0068] Figure 4 This is the selected area electron diffraction pattern of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1;
[0069] from Figure 3 Figure 4 It can be seen that the composite catalytic material is composed of 1T phase molybdenum disulfide and nickel disulfide (JCPDS No.11-0099).
[0070] Figure 5 The composition analysis results of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1;
[0071] from Figure 5 It can be seen that the atomic ratio of Mo and Ni in the composite catalytic material is close to 3:4, indicating that the molar ratio of molybdenum disulfide to nickel disulfide is 3:4. The S element is evenly distributed throughout the sphere, the Mo element is distributed in the spherical shell, and the Ni element is distributed in the spherical core, proving the core-shell structure of the composite material.
[0072] Figure 6 This is a transmission electron microscope image of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1;
[0073] from Figure 6It can be seen that the (002) interplanar spacing of MoS2 nanosheets is 0.85-0.90 nm, which is consistent with the 1T phase structure.
[0074] Figure 7 This is the full XPS spectrum of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1;
[0075] from Figure 7 It can be seen that the molybdenum disulfide-based composite catalytic material prepared in Example 1 contains a trace amount of N element. The introduction of N element can significantly increase the binding energy between polysulfide and the surface of the diaphragm, polarize the surface of the material, generate a dipole, and form a dipole-dipole electrostatic interaction with the polar polysulfide, ultimately providing sufficient surface binding force and restriction to the polar polysulfide, improving the loss of active substances and capacity attenuation of lithium-sulfur batteries, and improving battery performance.
[0076] Figure 8 This is the Raman spectrum of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1;
[0077] from Figure 8 It can be seen that the molybdenum disulfide in the molybdenum disulfide-based composite catalytic material prepared in Example 1 has a 1T phase structure.
[0078] Fig. 9 The X-ray diffraction spectra of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1 before and after being placed for 360 days;
[0079] from Fig. 9 It can be seen that the structural stability of the molybdenum disulfide in the molybdenum disulfide-based composite catalytic material prepared in Example 1 is very good, and the material still has a 1T phase structure after being placed for 360 days.
[0080] Fig.10 This is the X-ray diffraction spectrum of 1T phase MoS2 material (without NiS2 ball as substrate) before and after 90 days of storage;
[0081] from Fig.10 It can be seen that the T-phase molybdenum disulfide material transforms into a 2H phase structure after being placed for 90 days.
[0082] comprehensive Fig. 9 and Fig.10 It can be seen that the introduction of nickel disulfide substrate can promote the stability of the 1T phase structure of molybdenum disulfide.
[0083] Visible adsorption test:
[0084] Li2S6 solution (concentration of Li2S6 solution is 0.01M) was prepared by dissolving lithium sulfide (Li2S) and sulfur in a mixed solution of 1,3-dioxolane (DOL) and 1,2-dimethoxyethane (DME) in a molar ratio of 1:5 (volume ratio of DOL to DME is 1:1), and then stirred at 60°C for 5h. Then, 10mg of the molybdenum disulfide-based composite catalytic material prepared in Example 1 was added to 2mL of the Li2S6 solution in an Ar atmosphere, and digital photos before and after standing for 3 hours were taken, see Fig.11 As shown;
[0085] As a control, MoS2 was added to 2mL Li2S6 solution and the digital photos before and after standing for 3 hours are shown in Figure 2. Fig.11 As shown;
[0086] Fig.11 Digital photos of the 1T phase molybdenum disulfide-based composite catalyst material, MoS2, and Li2S6 solution prepared in Example 1 before and after standing for 3 hours;
[0087] from Fig.11 It can be seen that after standing for 3 hours, the color of the Li2S6 solution to which the molybdenum disulfide-based composite catalytic material prepared in Example 1 was added has changed from brown to transparent. This phenomenon indicates that the molybdenum disulfide-based composite catalytic material prepared in Example 1 has a strong adsorption effect on Li2S6.
[0088] Li2S nucleation test:
[0089] Sublimed sulfur and lithium sulfide (Li2S) were dissolved in a molar ratio of 1:7 and added to a DOL / DME solvent containing 1.0M LiTFSI (the volume ratio of DOL to DME was 1:1), and stirred in a water bath at 60°C for 24 hours to prepare a Li2S8 solution (the concentration of the Li2S8 solution was 0.25M). The experiment used 1mg of the 1T phase molybdenum disulfide-based composite catalytic material powder prepared in Example 1 to be coated on a carbon paper (CP) with a diameter of 13mm as the positive electrode, a lithium sheet as the negative electrode, and a commercial PP diaphragm (Celgard 2400) as the diaphragm to assemble a CR2032 model battery. Then, 20μL of Li2S8 solution was added to the cathode side, and 20μL of a blank electrolyte containing 2wt% LiNO3 was dripped into the anode side (the blank electrolyte was a DOL / DME solvent containing 1.0M LiTFSI (the volume ratio of DOL to DME was 1:1)). The assembled battery was first discharged to 2.06 V. Then, the Li2S deposition nucleation was carried out at 2.05 V. The deposition capacity of Li2S can be calculated by Faraday's law, see Fig.13 As shown;
[0090] As a control example, 1 mg of the 1T phase molybdenum disulfide-based composite catalytic material powder prepared in Example 1 was omitted from coating on the carbon paper (CP). The deposition capacity of Li2S can be calculated by Faraday's law, see Fig.12 As shown;
[0091] Fig.12 is the nucleation curve of lithium sulfide (Li2S) with carbon paper (CP) as electrode;
[0092] Fig.13 The nucleation curve of lithium sulfide (Li2S) of the 1T phase molybdenum disulfide-based composite catalytic material whose electrode is prepared in Example 1;
[0093] from Fig.13 It can be seen that the capacity of Li2S precipitated on the molybdenum disulfide-based composite catalytic material electrode prepared in Example 1 is 407 mAhg -1 , significantly higher than Fig. 9 The capacity of Li2S precipitated from carbon paper (135 mAh g -1 ). This result shows that the molybdenum disulfide-based composite catalytic material prepared in Example 1 can well promote the conversion of lithium polysulfide to Li2S, and has a good catalytic effect on inducing efficient nucleation and growth of Li2S.
[0094] Example 1 Preparation of 1T phase molybdenum disulfide-based composite catalytic material modified diaphragm (NiS2 / MoS2-CNTs):
[0095] 5 mg of the 1T-phase molybdenum disulfide-based composite catalytic material prepared in Example 1, 5 mg of carbon nanotubes and 22.2 mg of PVDF binder were uniformly mixed, and 5 mL of N-methylpyrrolidone (NMP) was added to form a suspension. The suspension was ultrasonically treated for 1 hour, and then the ultrasonically dispersed suspension was coated on a commercial polypropylene (PP) diaphragm (Celgard 2400) to obtain a diaphragm modified with the molybdenum disulfide-based composite catalytic material prepared in Example 1; after vacuum drying at 60° C. for 2 hours, it was punched into discs with a diameter of 19 mm.
[0096] As a control: the preparation method of MoS2 modified membrane (MoS2-CNTs) is as follows:
[0097] 5 mg MoS2, 5 mg carbon nanotubes and 22.2 mg PVDF binder were uniformly mixed, and 5 mL of N-methylpyrrolidone (NMP) was added to form a suspension. The suspension was ultrasonically treated for 1 h, and then the ultrasonically dispersed suspension was coated on a commercial polypropylene (PP) diaphragm (Celgard 2400) to obtain a MoS2-modified diaphragm (MoS2-CNTs); after vacuum drying at 60°C for 2 h, it was punched into discs with a diameter of 19 mm.
[0098] Assembly and electrochemical testing of lithium-sulfur batteries:
[0099] (1) Preparation of C / S positive electrode:
[0100] Sulfur powder and Kojin Black (KB) were uniformly ground in a mass ratio of 7:3. Then, they were heated at 155°C for 12 hours. After cooling to room temperature, the product was dispersed in NMP with Super P and PVDF in a mass ratio of 8:1:1, ultrasonically treated for 30 minutes, and then the mixed slurry was coated on aluminum foil as the positive electrode with an automatic coater. The prepared electrode was dried in a vacuum oven at 60°C for 12 hours. Finally, the electrode sheet was cut into discs with a diameter of 13 mm, and the sulfur loading was 1.3 mg / cm 2 .
[0101] Fig.14 is the thermogravimetric curve of C / S positive electrode; Fig.14 It can be seen that the carbon content in the positive electrode is 67%;
[0102] (2) Assembly of lithium-sulfur batteries
[0103] The electrochemical performance was tested using a battery model 2025, which was assembled in an argon-filled glove box. The C / S composite was used as the positive electrode, the lithium sheet was used as the negative electrode, and the diaphragms were the molybdenum disulfide-based composite catalytic material modified diaphragm prepared in Example 1, the MoS2-modified diaphragm lithium-sulfur battery, and the commercial PP diaphragm (Celgard 2400). The electrolyte used was 1.0 M lithium bis(trifluoromethane)sulfonyl imide (LiTFSI) in a DO / DME (volume ratio of 1:1) mixed solution containing 2 wt% LiNO3. The ratio of electrolyte to sulfur was 15 μL mg -1 .
[0104] (3) Electrochemical test
[0105] The constant current charge and discharge (GCD) experiment was carried out on a LANHE CT3002A. The potential range was 1.7-2.8 V. The cyclic voltammetry (CV) curve was tested on a VMP3 electrochemical workstation (BioLogic, France) with a scan rate of 0.1 mV / s and a voltage range of 1.7-2.8 V. The measurement frequency range of electrochemical impedance spectroscopy (EIS) was from 0.01 Hz to 100 kHz.
[0106] Fig.15 The CV curves of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1 are modified diaphragm lithium-sulfur battery, MoS2-modified diaphragm lithium-sulfur battery and PP diaphragm lithium-sulfur battery;
[0107] from Fig.15It can be seen that at 0.1 mV / s, the CV curve area of the lithium-sulfur battery using the molybdenum disulfide-based composite catalytic material prepared in Example 1 to modify the diaphragm is larger, and the cathode peak and the anode peak show an obvious inward shift, indicating that the lithium-sulfur battery using the molybdenum disulfide-based composite catalytic material prepared in Example 1 to modify the diaphragm has a lower electrochemical polarization and faster redox kinetics, indicating that the molybdenum disulfide-based composite catalytic material prepared in Example 1 can anchor lithium polysulfide well, weaken the shuttle effect, and improve battery performance.
[0108] Fig.16 The impedance spectra of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1 are modified diaphragm lithium-sulfur battery, MoS2-modified diaphragm lithium-sulfur battery and PP diaphragm lithium-sulfur battery;
[0109] from Fig.16 It can be seen that the lithium-sulfur battery with a diaphragm modified by the molybdenum disulfide-based composite catalytic material prepared in Example 1 has a smaller semicircular diameter in the high-frequency region and exhibits better charge transfer characteristics.
[0110] Fig.17 The rate characteristics of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1 are modified diaphragm lithium-sulfur battery, MoS2-modified diaphragm lithium-sulfur battery and PP diaphragm lithium-sulfur battery;
[0111] from Fig.17 It can be seen that under 0.1C conditions, the capacity is 1437mAhg -1 ; Under 5C conditions, the capacity is 722mAhg -1 When the current density returns to 0.1C, the capacity can still reach 1230mAhg -1 It is shown that the lithium-sulfur battery with a diaphragm modified by the molybdenum disulfide-based composite catalytic material prepared in Example 1 has good rate performance.
[0112] Fig.18 The cycle characteristics of the 1T phase molybdenum disulfide-based composite catalytic material prepared in Example 1 are modified diaphragm lithium-sulfur battery, MoS2-modified diaphragm lithium-sulfur battery and PP diaphragm lithium-sulfur battery;
[0113] from Fig.18 It can be seen that under 0.2C conditions, 1228mAh g -1 The initial capacity of the battery can be maintained at 85% after 100 cycles; the initial capacity is 1154 mAh g at 0.5C. -1 During the 250-cycle cycle, the decay rate per cycle is only 0.099%; under 1C conditions, the initial capacity is 931mAhg -1 During the 1000-cycle cycle, the attenuation rate per cycle is only 0.051%.
[0114] Example 2: The difference between this example and Example 1 is that the amount of nickel disulfide core and ammonium molybdate tetrahydrate is changed so that the molar ratio of Mo:Ni is 1:2, 1:1, and 3:1. The other steps and parameters are the same as those in Example 1.
[0115] The 1T phase molybdenum disulfide-based composite catalytic materials prepared with four Mo:Ni ratios in Example 1 and Example 2 were used to prepare the diaphragm and assemble the battery, and the cycle performance of the battery was tested. The cycle performance of the battery was different with different Mo:Ni ratios. Among them, when the molar ratio of Mo:Ni was 2:1, the performance of the battery was the most stable. The initial capacity of the battery was 1226mAh g -1 , the capacity retention rate is 62% after 100 cycles.
[0116] Fig.19 Performance diagram of the battery assembled by preparing a diaphragm and assembling a battery using 1T-phase molybdenum disulfide-based composite catalytic material prepared by changing the Mo:Ni ratio, where (a) is the cycle performance and (b) is the initial capacity and capacity retention rate at 0.1C.
Claims
1. A 1T phase molybdenum disulfide-based composite catalytic material, characterized in that A 1T phase molybdenum disulfide-based composite catalytic material is a micron ball with a core-shell structure, with a diameter of 1.5μm to 5.0μm, wherein the core is a compact sphere composed of nickel disulfide nano-flaky crystals, with a diameter of 1.0μm to 4.0μm, and the shell is a wrinkled and fluffy shell composed of thermodynamically stable 1T phase molybdenum disulfide nanosheets, with a thickness of 0.2μm to 1μm, and flower-shaped molybdenum disulfide nanosheets are perpendicular to the surface of the micron ball and wrapped in the outer layer to form a three-dimensional network structure; the lateral size of the flower-shaped molybdenum disulfide nanosheets is 50 to 800nm, the thickness is 5-30nm, and the (002) crystal plane spacing is 0.85 to 0.90nm, which is consistent with the 1T phase structure.
2. A 1T phase molybdenum disulfide-based composite catalytic material according to claim 1, characterized in that The molar ratio of nickel disulfide to molybdenum disulfide in the 1T phase molybdenum disulfide-based composite catalytic material is (1-3):(1-2), and a small amount of N element is contained in the material.
3. The method for preparing a 1T phase molybdenum disulfide-based composite catalytic material according to claim 1, characterized in that The preparation method is specifically completed according to the following steps:
1. Preparation of nickel disulfide core: First, Ni(NO3)2·6H2O is added to deionized water and stirred until dissolved, and then Na2S2O3·5H2O is added and stirred until dissolved to obtain a mixture; the mixture is poured into a high-pressure reactor, subjected to hydrothermal reaction for a period of time, cooled to room temperature, and then centrifugally washed and vacuum dried to recover the product to obtain a nickel disulfide spherical core; 2. Preparation of 1T phase MoS2-based composite catalytic materials: Under ultrasonic conditions, nickel disulfide spherical cores are dispersed in ultrapure water, and then ammonium molybdate tetrahydrate and thiourea are added and stirred evenly to obtain a black mixed solution; the black mixed solution is poured into a high-pressure reactor, subjected to hydrothermal reaction for a period of time, cooled to room temperature, and then centrifuged and washed and vacuum dried to recover the product to obtain a 1T phase molybdenum disulfide-based composite catalytic material.
4. The method for preparing a 1T phase molybdenum disulfide-based composite catalytic material according to claim 3, characterized in that The mass ratio of Ni(NO3)2·6H2O described in step 1 to the volume ratio of deionized water is (1g~2g):50mL; the mass ratio of Na2S2O3·5H2O described in step 1 to the volume ratio of deionized water is (1.g~2g):50mL.
5. The method for preparing a 1T phase molybdenum disulfide-based composite catalytic material according to claim 3, characterized in that The temperature of the hydrothermal reaction in step 1 is 150° C. to 170° C.; the time of the hydrothermal reaction in step 1 is 19 h to 21 h.
6. The method for preparing a 1T phase molybdenum disulfide-based composite catalytic material according to claim 3, characterized in that The centrifugal washing described in step one uses deionized water as a cleaning agent, and the centrifugal washing is performed 2 to 4 times. The speed of each centrifugal washing is 3000 r / min to 8000 r / min, and the time of each centrifugal washing is 5 min to 10 min. The temperature of the vacuum drying described in step one is 50°C to 70°C, and the time of the vacuum drying is 6 h to 24 h.
7. The method for preparing a 1T phase molybdenum disulfide-based composite catalytic material according to claim 3, characterized in that The mass ratio of the nickel disulfide core described in step 2 to the volume ratio of ultrapure water is (0.2g~0.4g):100mL; the mass ratio of the ammonium molybdate tetrahydrate described in step 2 to the volume ratio of ultrapure water is (0.5g~1.2g):100mL; the mass ratio of the thiourea described in step 2 to the volume ratio of ultrapure water is (1.2g~1.7g):100mL.
8. The method for preparing a 1T phase molybdenum disulfide-based composite catalytic material according to claim 3, characterized in that The temperature of the hydrothermal reaction in step 2 is 170° C. to 190° C.; the time of the hydrothermal reaction in step 2 is 14 h to 16 h.
9. The method for preparing a 1T phase molybdenum disulfide-based composite catalytic material according to claim 3, characterized in that The centrifugal washing described in step 2 uses deionized water as a cleaning agent, and the centrifugal washing is performed 2 to 4 times. The speed of each centrifugal washing is 1000 r / min to 10000 r / min, and the time of each centrifugal washing is 5 min to 20 min. The temperature of the vacuum drying described in step 2 is 50°C to 70°C, and the time of the vacuum drying is 6h to 24h.
10. Use of a 1T phase molybdenum disulfide-based composite catalytic material prepared by the preparation method according to claim 1, characterized in that A 1T phase molybdenum disulfide-based composite catalytic material is used as a positive electrode host, a separator or an interlayer of a lithium-sulfur battery or a sodium-sulfur battery.